2004
DOI: 10.1021/jp048873t
|View full text |Cite
|
Sign up to set email alerts
|

A Product Yield Study of the Reaction of HO2 Radicals with Ethyl Peroxy (C2H5O2), Acetyl Peroxy (CH3C(O)O2), and Acetonyl Peroxy (CH3C(O)CH2O2) Radicals

Abstract: The reaction between HO2 and RO2 radicals represents an important chemical sink for HO x radicals in the atmosphere. On the basis of a few product yield studies, these reactions are believed to form hydroperoxides almost exclusively (R8a), although several different reaction channels may be thermodynamically accessible (R8a−d):  RO2 + HO2 → ROOH + O2 (R8a); RO2 + HO2 → ROH + O3 (R8b); RO2 + HO2 → RO + OH + O2 (R8c); and RO2 + HO2 → R‘CHO + H2O + O2 (R8d). Branching ratios for reaction R8 were measured for thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
255
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(287 citation statements)
references
References 35 publications
26
255
5
Order By: Relevance
“…Recent studies proposed that a new channel of PA + HO 2 reaction can be important with a branching ratio of 0.4 Hasson et al, 2004;Jenkin et al, 2007), through which CH 3 O 2 is produced, and therefore this new finding can be a potential HCHO source. We added the new HCHO producing channel of PA + HO 2 reaction in the HCHO production calculation (Eq.…”
Section: Appendix a Estimate Of Photolysis Rate Constantsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies proposed that a new channel of PA + HO 2 reaction can be important with a branching ratio of 0.4 Hasson et al, 2004;Jenkin et al, 2007), through which CH 3 O 2 is produced, and therefore this new finding can be a potential HCHO source. We added the new HCHO producing channel of PA + HO 2 reaction in the HCHO production calculation (Eq.…”
Section: Appendix a Estimate Of Photolysis Rate Constantsmentioning
confidence: 97%
“…The HCHO production mechansim via CH 4 oxidation is described in detail by Fried et al (1997). The lifetime of CH 4 at 298K with 6 × 10 6 molecule cm −3 OH is ∼10 months (Atkinson et al, 2006), and hence it is assumed that CH 4 is homogeneously distributed throughout the boundary layer at a concentration of 1.774 ppm (IPCC, 2007 Grosjean and Grosjean (1995) Fantechi et al (1999), 0.29 from Alvarado et al (1999), and 0.36 from Grosjean and Grosjean, 1995 al., 2006; Klotz et al, 2001;Koch and Moortgat, 1998;LaFranchi et al, 2009;Orlando et al, 1999;Tuazon and Atkinson, 1989 Hasson et al, 2004;Jenkin et al, 2007), which, upon decomposition and reaction with O 2 forms CH 3 O 2 (Reactions R13-R15 in Appendix C). We assume that CH 3 O 2 is rapidly converted into HCHO.…”
Section: Peroxy Radicals and Glycolaldehyde As Hcho Precursorsmentioning
confidence: 99%
“…Hasson et al (2004) observed, using chamber studies and measuring stable products, that certain peroxy radical + hydroperoxy radical reactions such as the title reaction of acetylperoxy, CH 3 C(O)O 2 , can lead to the formation of OH radicals through a third channel (Reaction R5c). Previous studies had assumed radical termination through Reaction (R5a) (α (R5a) = k (R5a) /k (R5) = 0.8) and Reaction (R5b) (α (R5b) = k R5b /k R5 = 0.2) (Lightfoot et al, 1992;Moortgat et al, 1989;Crawford et al, 1999).…”
mentioning
confidence: 99%
“…Orlando and Tyndall (2003) were able to demonstrate that an underestimated IR cross-section for peracetic acid, CH 3 C(O)OOH (Reaction R5a), had led to the assignment of α (R5a) 3 times too high. Based on this revised cross-section, Hasson et al (2004) measured yields of (0.40 ± 0.16) : (0.20 ± 0.08) : (0.40 ± 0.16) for α (R5a) : α (R5b) : α (R5c) . In equivalent reactions of the alkyl peroxy radical, C 2 H 5 O 2 , with HO 2 , only channel (Reaction R4a) producing C 2 H 5 OOH + O 2 was observed.…”
mentioning
confidence: 99%
“…The differences of the ratios could also be caused by additional OH recycling via HO 2 + RO 2 reactions that gain importance under low-NO conditions. Such radical-radical reactions that are usually thought to produce non-radical products can lead to enhanced OH recycling as shown by recent laboratory studies for reactions of carbonyl-containing RO 2 radicals with HO 2 (Hasson et al, 2004(Hasson et al, , 2012Jenkin et al, 2007Jenkin et al, , 2008Jenkin et al, , 2010Dillon and Crowley, 2008;Groß et al, 2014). Recently also OH formation for the reaction of HO 2 with bicyclic peroxy radicals from aromatic precursors was proposed with a rate constant k 9 as used in the previous section.…”
Section: Discussionmentioning
confidence: 96%